Deeply Superficial Andy Warhols Amerika-Images der 1950er und 1960er als Kulturkritik - Deiss, Mélanie-Chantal (Image, 2015)
In place of the entanglement of person and work that so strongly marks the artistic work of Andy Warhol, and settles it in the usual Pop Art context, Mèlanie-Chantal Deiss locates it within the cultural context of America's post-war period. Viewed from this perspective, Warhol's work - which tends to be classified as superficial and ahistorical - exhibits unexpectedly serious engagements with concerns of the 1950s and 1960s. Throughout his image series, expressive, somewhat ambivalent narrative strands from America's post-war period unfurl, which transmit a concrete image, as a kind of written historical document. Warhol's visualized narration ultimately culminates in a cultural critique, which treats America not just as a stage of images, but also as site of contemplation of a cultural imaginary, in which art can critically and productively intervene.